PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING DALAM PEMBELAJARAN IPAS KELAS V MIS AWALUDDIN KUBU RAYA - Meidianti, Hesty Zenitha; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study generally aims to develop a Discovery Learning-based Student Worksheet (LKPD) for fifth-grade elementary school students that is feasible and practical for supporting IPAS (Integrated Science) learning activities. The research employs the ADDIE method. The study participants include a homeroom teacher, 16 students from class VB at MIS Awaluddin Kubu Raya, and two expert validators, who are lecturers. The data collection technique used in this research is a questionnaire.The research results indicate that the development of the Discovery Learning-based Student Worksheet (LKPD) has gone through five stages: analysis, design, development, implementation, and evaluation. The feasibility of the developed Discovery Learning-based Student Worksheet (LKPD) was rated as "highly feasible" by expert validators, achieving scores of 82.5% for didactic requirements, 91.4% for construction requirements, and 96.7% for technical requirements, making it suitable for trial use. It also met the "Highly Practical" category, receiving a 90.8% approval rating from students, indicating that the Discovery Learning-based Student Worksheet (LKPD) is both feasible and practical for use in the learning process.